Efficient Exciton Diffusion in Organic Bilayer Heterojunctions with Nonfullerene Small Molecular Acceptors - Lee, Tack Ho; Park, Song Yi; Park, Won-Woo; Du, Xiaoyan; Son, Jae Hoon; Li, Ning; Kwon, Oh-Hoon; Woo, Han Young; Brabec, Christoph; Kim, Jin Young (ACS Energy Letters, 2020)
Solution-processed bilayer organic solar cells (OSCs) with high performance are demonstrated for nonfullerene small molecular acceptors (NFAs). Unlike fullerene acceptors, NFAs show significant spectral overlap between their absorption and the photoluminescence (PL) of a polymer donor, which makes the design of an efficient exciton-harvesting bilayer heterojunction possible. Efficient exciton diffusion in the organic bilayer heterojunction is realized by long-range energy transfer between a polymer donor and NFAs. We observed efficient exciton diffusion from the polymer/NFA bilayer heterojunctions via thickness-dependent PL quenching and time-resolved PL measurements. Despite the strongly reduced donor-acceptor interface area, a substantial density of charge-transfer states is observed for the polymer/NFA bilayer heterojunctions by electroluminescence measurements. Overall, polymer/NFA bilayer heterojunction OSCs demonstrate a power conversion efficiency of 9%-10%, which is comparable to the photovoltaic performance of bulk heterojunction OSCs, with the additional advantage of simplified microstructure formation.
Created from Fastlane, WoS look-up